PERBEDAAN PENINGKATAN AGILITYDAN PENINGKATAN PEMAIN BASKET ANTARA PEMAIN BASKET SMALL MAN DAN BIG MAN DENGAN PEMBERIAN LATIHAN LADDER DRILL (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractBackground: Basketball is a team sport. The difference between humans small and Bigman it's not about size, but this is about the position of the player. The little guy is a player out of position like the pont guard, shooting guard and small forward and Bigman is a basketball player at the position under such a power forward and center as a player. The main difference of the work makes a difference in characteristics including agility. Agility is very important in basketball. Agility can be improved with practice, but because there are differences betwen the characteristics, so that could be the result of differences in training for small agilty man and Bigman. Ladder drill exercise is one exercise that aims to improve agility. Forms of exercise walking, jumping and sliding in the box that makes like a staircase on the second floor. The person must be run, or jump through a staircase. Objective: The aim of this study was to determine the differences between humans increases the agility of small and large people after exercise drill ladder. Example: The sample is a basketball player who has played for at least 2 years. There are 20 basketball players and they are divided into two groups. One group is the little man by ladder and the other exercises are great people who were also given training drill ladder. Exercise ladder commonly used for basketball players and was included in the training program basketball player. So the researchers gave the exercise of their own players without giving Researcher Training Methods: This quasi-experimental, where this measure agility between the two groups after the exercise drill ladder. Agility will be measured by Test Hexagonal Obstacle. samples will be tested after six weeks programmed. results; The hexagonal obstacle test scores in the second desciribed, Results: The mean man hexagonal small test before 12.59 seconds (sd = 1,242) and after exercise 12.27 seconds (sd = 0833), and, the results of the test hexagonal constraints Bigman is the mean average before 13.03 seconds (sd = 0950) and after the exercise of 11.24 seconds (sd = 1344) hypothesis is tested by independent T test and the result was p = 0.009 <@ 0:05 So researchers suggest there needs to be another exercise the power of intelligence such reseach pylomteric exrcise Conclusion; There is a difference in improving agility between the small and the big man after a workout drill ladder for basketball players. Keywords: Small man, big man, agility AbstrakLatar Belakang: Basket adalah olahraga tim. Perbedaan antara manusia kecil dan Bigman itu bukan tentang ukuran tetapi ini adalah tentang posisi pemain. Orang kecil adalah pemain di luar posisi seperti penjaga pont, shooting guard dan small forward dan Bigman adalah pemain di posisi basket di bawah seperti power forward dan center sebagai pemain. Perbedaan dari pekerjaan utama membuat perbedaan dalam karakteristik termasuk kelincahan. Agility sangat penting dalam basket. Agility dapat ditingkatkan dengan latihan, tetapi karena ada perbedaan betwen karakteristik, sehingga bisa menjadi hasil perbedaan latihan untuk agilty small man dan Bigman. Tangga latihan drill adalah salah satu latihan yang bertujuan untuk meningkatkan kelincahan. Bentuk latihan berjalan, melompat dan meluncur di dalam kotak yang membuat seperti tangga di lantai. Orang tersebut harus dijalankan, atau melompat melalui tangga. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui perbedaan kelincahan yang meningkat antara manusia kecil dan orang besar setelah latihan drill tangga. Contoh: Sampel adalah pemain basket yang sudah bermain selama minimal 2 tahun. Ada 20 pemain basket dan mereka dibagi menjadi dua kelompok. Satu kelompok adalah laki-laki kecil yang diberi tangga latihan dan yang lainnya adalah orang besar yang juga diberi latihan drill tangga. Latihan tangga yang umum digunakan untuk pemain basket dan itu termasuk dalam program latihan pemain bola basket. Jadi Peneliti memberikan latihan dari pemain tanpa memberi Peneliti sendiri Metode Latihan: Ini kuasi eksperimental, di mana ini mengukur kelincahan antara dua kelompok setelah latihan drill tangga. Agility akan diukur oleh Hexagonal Uji Kendala. sampel akan diuji setelah enam minggu diprogram. Hasil; skor tes kendala heksagonal itu desciribed di kedua, Hasil: Hasil heksagonal uji small man berarti sebelum 12,59 detik (sd = 1.242) dan setelah latihan 12,27 detik (sd = 0.833), dan, hasil kendala heksagonal tes Bigman adalah rata-rata sebelum 13,03 detik (sd = 0.950) dan setelah latihan 11,24 detik (sd = 1.344) hipotesis diuji dengan uji T independen dan hasilnya adalah p = 0,009 <@ 0.05 Jadi Peneliti menyarankan ada perlu lain latihan reseach kekuatan kecerdasan seperti pylomteric exrcise Kesimpulan; Ada perbedaan dalam kelincahan meningkatkan antara manusia kecil dan orang besar setelah latihan drill tangga untuk bola basket pemain. Kata kunci: Small man, big man, agility